Novel integrated 3D multidetector computed tomography and fluoroscopy fusion for left atrial appendage occlusion procedures. Issue 2 (17th March 2017) - Roy, A.K.; Horvilleur, J.; Cormier, B.; Cazalas, M.; Fernandez, L.; Patane, M.; Neylon, A.; Spaziano, M.; Sawaya, F.J.; Arai, T.; Bouvier, E.; Hovasse, T.; et al.
Abstract : Objectives: This report demonstrates the application and feasibility of novel 3D‐MDCT real‐time fusion technology with fluoroscopy, for left atrial appendage (LAA) occlusion procedures. Background: A successful LAA occlusion procedure relies on multiple imaging modalities, including TEE or 3D‐MDCT, and fluoroscopy. Effectively integrating these imaging modalities may improve implantation safety and success. To our knowledge this technique has not been previously described for LAA occlusions. Methods: This observational study compared clinical and procedural parameters for procedures performed with or without fusion integration. All patients had a pre‐procedural 3D‐MDCT for LAA measurements, along with 3D analyses of LAA morphology and surrounding structures. Using the image fusion software (Valve ASSIST 2, GE Healthcare, UK), landmarks were identified on fluoroscopy, and MDCT LAA anatomy outlines were then projected onto the real‐time fluoroscopy image during the procedure, to guide all steps of the intervention. Results: A total of 57 patients underwent LAA occlusion, with 16 performed using fusion software. In comparison to the pre‐fusion group, reductions in contrast volume (21.0 ± 11.7 vs. 95.9 ± 80.5 ml, P < 0.001), procedure time (63.0 ± 22.0 vs. 87.3 ± 43.0 min, P = 0.01), and fluoroscopy time (6.2 vs. 8.3 min, P = 0.03) were observed. Incomplete sealing (0 vs. 14.6%, P = 0.16) and device deployment success (100 vs. 92.7%, P = 0.17) were not significantly different. Conclusions: The addition of this novel fusion technology is safe and feasible. To optimize LAA procedural success, fusion integration may offer a promising addition, or alternative, to current imaging modalities. © 2017 Wiley Periodicals, Inc.